The Potential of Goat Meat Acceptance by Young Adults in South Africa - Karina Palmer; Ashika Naicker; Unathi Kolanisi (African Journal of Inter-Multidisciplinary Studies, 2022)
Recent global meat consumption trends report an increase in goat meat consumption as a protein source; however, consumption is not popular in South Africa. Despite goat meat being a nutritious and sustainable source, the willingness to consume goat meat as an acceptable protein source among young adults is not known. The study aims to explore factors that may prevent goat meat consumption and determine the potential for goat meat consumption among young adults from a rural and urban university in KwaZulu-Natal, South Africa. An online meat consumption survey was developed and disseminated through email to students (n=416). Goat meat consumption by young adults was reported to be mainly due to cultural practices. Although most of the participants consumed goat meat, the frequency of consumption was lower than that of chicken, beef and pork. Key barriers to goat meat consumption included a lack of availability, unappealing aroma and allergies. The findings indicated the potential to promote goat meat availability at retail outlets in South Africa, specifically through value-added convenience products. An integrated approach, including consumer education and the increasing availability of goat meat and value-added products, will improve the consumption of this sustainable and nutritious protein source.